Living Fatwa: Studi Fatwa DSN-MUI Tentang Jasa Keperantaraan di Indonesia - Mustakim, Andi Ardiyan; Indonesia; Islahudin, Ahmad Noor; Fitriyah, Faridatul; Masduki, M. Alwan (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Meto, 2025)
This article aims to examine the transformation of fatwas of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) regarding brokerage services in the perspective of living fatwa. The main issue raised is the weak binding power of religious fatwas in the realm of positive law, which often causes fatwas to be ignored in the public policy-making process. However, DSN-MUI fatwas related to brokerage services have proven to make a significant contribution in inspiring the formation of legal norms contained in legislation in the banking sector and financial transactions in Indonesia. Therefore, the focus of this article is directed at the study of fatwas on brokerage services as a representation of normative-religious norms in banking practices and financial transactions. Thus, it complements other studies on living fatwas. This article examines how fatwas on brokerage services have been transformed into a living norm in the Indonesian regulatory context, and identifies the main characteristics underlying this transformation. This research is a literature review with a living fatwa approach. The results show that the transformation of Islamic norms in the form of fatwas on brokerage services has a strategic role in influencing the birth of regulations that integrate sharia principles into the national legal system, especially in the field of transactions and finance. The laws and regulations governing brokerage services in Indonesia can be understood as a form of “institutionalization” of the norms previously formulated through the DSN-MUI fatwa. This article argues that these fatwas perform two main functions: first, as a reinforcement of state policy for the public good (ta'yidi); and second, as a normative source in the formulation and making of public policy (insya'i). Furthermore, DSN-MUI fatwas that have undergone transformation into the national legal system in a living perspective display characteristics that are implementative, visionary, scientific, and responsive to social dynamics (dynamic movement).